Professional iPhone and iPad application development - Backlin, Gene (Programmer to programmer., 2011)
"The topics covered in this book use the current SDK 4.0 for iPhone and iPod Touch, and the SDK 3.2 for the iPad, Xcode and Interface Builder are the main tools used to create all the applications presented"--Page xxiii